Co-Ni-Cr-Mo 합금의 열간가공조건 연구 - 이백희; 이규환; 김영도 (한국생체재료학회, 2002)
Hot forming condition of Co-Ni-Cr-Mo alloy (MP35N) was studied with increase of mechanical property by using THERMECMASTOR. The Co-Ni-Cr-Mo alloy was forged for near shape in high temperature, and then made up a finished product using precision machining when the alloy was made for the joint prostheses. In this study, the deformation behavior of the Co-Ni-Cr-Mo alloy was investigated with temperature and deformation rate for the most suitable hot forming condition by using THERMECMASTOR.